The relationship between front crawl performance and hydrodynamics in young female swimmers - Marinho, D. A.; Oliveira, R.; Garrido, N. D.; Barbosa, T. M.; Costa, M. J.; Silva, A. J.; Costa, A. M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The aim of this study was to analyse the relationship between front crawl performance and hydrodynamic variables during leg kicking. Sixteen female swimmers (9.2±0.6 years) participated in this study. The 200m front crawl performance, the 200m front crawl kicking performance and the active drag during leg kicking were measured. The velocity perturbation method was used to determine active drag. The 200m front crawl performance was significantly correlated with performance in 200m kicking (0.89), with hydrodynamic drag force during leg kicking (-0.70), and power output in kicking (-0.64). Drag coefficient was not related to the performance in 200 m front crawl. These findings underline the importance of leg kicking to performance in front crawl swimming in these ages and suggests the important role of kicking tasks during training in young swimmers.